2011
DOI: 10.1074/jbc.m111.251025
|View full text |Cite
|
Sign up to set email alerts
|

Probing the HIV gp120 Envelope Glycoprotein Conformation by NMR

Abstract: The HIV envelope glycoprotein gp120 plays a critical role in virus entry, and thus, its structure is of extreme interest for the development of novel therapeutics and vaccines. To date, high resolution structural information about gp120 in complex with gp41 has proven intractable. In this study, we characterize the structural properties of gp120 in the presence and absence of gp41 domains by NMR. Using the peptide probe 12p1 (sequence, RINNIPWSEAMM), which was identified previously as an entry inhibitor that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…For these experiments we chose standard pulse sequences depicted in Fig. 1a (Dalvit et al, 2001; Mayer and Meyer, 2001), which we have found to be relatively easy to implement and robust for studies designed to discover drug-like ligands, characterize their interaction, and guide chemical improvement (Celigoy et al, 2011; McCullough et al, 2012; Antanasijevic et al, 2013; Basu et al, 2013; Ramirez et al, 2014). It is also important to determine the experimental protocol to be used to fairly compare the two experiments.…”
Section: Resultsmentioning
confidence: 99%
“…For these experiments we chose standard pulse sequences depicted in Fig. 1a (Dalvit et al, 2001; Mayer and Meyer, 2001), which we have found to be relatively easy to implement and robust for studies designed to discover drug-like ligands, characterize their interaction, and guide chemical improvement (Celigoy et al, 2011; McCullough et al, 2012; Antanasijevic et al, 2013; Basu et al, 2013; Ramirez et al, 2014). It is also important to determine the experimental protocol to be used to fairly compare the two experiments.…”
Section: Resultsmentioning
confidence: 99%
“…54,55 Water was selectively saturated using a 2 ms square shaped pulse with a mixing time of 2 s and a relaxation delay of 2.5 s. STD experiments were performed as previously described. 56,57 In these experiments, protein 1H was saturated with a train of 50 ms Gaussian-shaped pulses at 100 Hz power for 1 s with “on” resonance saturation at −1 ppm and “off” resonance saturation at 30 ppm (the relaxation delay was 2.5 s before the saturating pulses). Spectra were processed by NMRPipe with a 5 Hz line broadening function and analyzed by NMRDraw.…”
Section: Methodsmentioning
confidence: 99%
“…WaterLOGSY (water ligand observed via gradient spectroscopy) experiments were performed as previously described (37,38), with a relaxation delay of 2.5 s, a mixing time of 2 s, and 1,024 scans (or 5,120 scans for the competition experiments). Saturation transfer difference (STD) experiments were performed as previously described (39)(40)(41), with a relaxation delay of 2.5 s, a saturation time of 1 s, and 256 scans with "on" resonance saturation at Ϫ1.5 ppm and "off" resonance saturation at 30 ppm. Nuclear Overhauser effect (NOE) spectroscopy (NOESY) experiments were performed as previously described (42), with a mixing time of 1 s and 24 scans.…”
Section: Methodsmentioning
confidence: 99%
“…4B) further suggests that MBX2329 and MBX2546 bind to sites that are Ͼ6 Å apart. We further examined the binding epitopes of MBX2329 and MBX2546 for H5 HA by an STD NMR experiment, which identifies 1 H in closest proximity to the protein surface (39,41). The relative STD for the interaction between MBX2329 and H5 HA is shown in Fig.…”
Section: Identification Of New Influenza Virus Entry Inhibitorsmentioning
confidence: 99%